Multidrug Resistance Is Mediated by Large Plasmids Carrying a Class 1 Integron in the Emergent Salmonella enterica Serotype [4,5,12:i:−] - Guerra, Beatriz (American Society for Microbiology, 2001)
A multidrug-resistant Salmonella enterica serotype [4,5,12:i:−] clone carried a class 1 integron harboring dfrA12 and aadA2 gene cassettes and bla(TEM-1), aac(3)-IV, cmlA1, and tetA genes located in large plasmids of about 140 kb (carrying spv) or 120 kb (lacking spv). Several segregants, lacking multidrug resistance, contained a plasmid smaller than the parental one and no longer hybridized with probes for the lost resistances. The genes mediating resistance to ampicillin, chloramphenicol, and tetracycline in the [4,5,12:i:−] clone are different from those found in the pentadrug-resistant serotype Typhimurium DT104 clone.